Improved probability density function using modified-AND detection technique for incoherent SAC-OCDMA systems - Hamza Mohammed Ridha, Al-Khafaji; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage http://ieeexplore.ieee.org/